Bimbingan Kewirausahaan bagi Industri Roti Rumahan Klien Balai Pemasyarakatan Kelas II Metro - Desta Ayu Valentin; Umar Anwar (UIN Fatmawati Sukarno Bengkulu, 2022)
Correctional centers have the function and task of carrying out some of the main tasks of the Director General of Corrections in providing guidance to correctional clients in their area. The guidance provided by the Correctional Center can be in the form of work skills, one of which is entrepreneurship. One of the clients at the Class II Metro Correctional Center has a home-based bakery industry that has an impact on the client's income and future. Therefore, this study aims to determine the form of mentoring as well as the entrepreneurial process and results of the client's home bakery industry and also to find out what factors influence the home bakery production process and whether the motivation of the correctional client can affect the success of the home bakery industry production. The method in this study uses qualitative research methods with descriptive data analysis techniques in the form of case study approaches and literature studies. Data collection techniques used in this study were interviews, observation, and literature study. The results of this study indicate that the form of guidance carried out by Fathers can be in the form of personal or group guidance, namely with entrepreneurship training which will later produce a product in the form of home-made bread and the factors that influence the production process of home-made bread belonging to the correctional client including: equipment , raw materials and labor as well as the motivation of these correctional clients can affect the success of the home bakery industry production.